Intra-Articular Injections of Curcumin Monoglucuronide TBP1901 Suppresses Articular Cartilage Damage and Regulates Subchondral Bone Alteration in an Osteoarthritis Rat Model. (December 2021) - Nakahata, Akihiro; Ito, Akira; Nakahara, Ryo; Kishimoto, Atsuhiro; Imaizumi, Atsushi; Hashimoto, Tadashi; Mukai, Shogo; Nakagawa, Yasuaki; Kuroki, Hiroshi
Objective: Curcumin monoglucuronide (TBP1901) is highly water soluble and can convert to free form curcumin, which has pharmacological effects, on intravenous administration. This study aimed to investigate the effectiveness of TBP1901 intra-articular injections in an osteoarthritis (OA) rat model. Methods: Sixty-four male Wistar rats (12 weeks old) who underwent destabilized medial meniscus (DMM) surgery were randomly separated into the TBP1901 injection or saline solution (control) injection group. They were sacrificed at 1, 2, 6, or 10 weeks postoperatively (weeks 1, 2, 6, and 10; n = 8 for each group). TBP1901 (30 mg/mL) or saline solution of 50 μL was injected into the knee joints twice a week during weeks 1 and 2 to investigate the effects in the acute phase of posttraumatic (PT) OA or once a week during weeks 6 and 10 to investigate it in the chronic phase of PTOA. Histology, immunohistochemistry, and micro-computed tomography were performed to evaluate the changes in OA. Results: TBP1901 injections significantly reduced synovial inflammation at weeks 1 and 2, and tumor necrosis factor-α expression in the articular cartilage at week 6. The TBP1901 injections also significantly suppressed articular cartilage damage, subchondral bone (SB) plate thickening, SB plate perforation, and osteophyte formation at week 10. Conclusions: TBP1901 intra-articular injections suppressed synovial inflammation in the acute phase of PTOA in DMM rats. In the chronic phase, TBP1901 suppresses articular cartilage damage and regulates SB plate changes.